PEMBELAJARAN HYBRID LEARNING SEBAGAI UPAYA PENINGKATAN MUTU PEMBELAJARAN DI SEKOLAN DASAR PADA MASA PANDEMI - Ni Putu Candra Prastya Dewi; Ni Luh Ika Windayani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The implementation of distance learning (PJJ) which has been carried out online from the beginning of the pandemic to the present, is feared to have a negative effect on the psychosocial aspects of students, so there is a need for changes related to online learning techniques which were previously purely in the network so that a combination of offline learning is carried out (outside the network). ) or offline (face to face). This combination is found in the Hybrid Learning model. Hybrid learning itself combines face-to-face learning activities with computer and internet technology-based learning. The purpose of this study was to determine the implementation of hybrid learning in elementary schools. Data collection techniques in this study were carried out by interviewing 10 elementary school teachers in the city or in the village in Bali and 3 elementary school students in Bali. The results showed that both teachers and students were very happy with hybrid learning because in addition to making it easier for teachers to teach, it also gave students enthusiasm for learning because students had the opportunity to interact directly with either the teacher or with their friends.Keywords: Hybrid Learning, Online Learning, Offline Learning